Development of a prototype ignition system with electrical system setup in a formula student racing car / Muhammad Amir Danial Che Rosli - Che Rosli, Muhammad Amir Danial (2024)
This project presents an Ignition System with an Electrical System Setup in A Formula Student Racing car. This project is to achieve engine reliability and performance, efficient combustion and enhance overall vehicle performance while adhering to safety rules and budgetary restrictions. This project has achieved the main objective which is to design and fabricate an efficient and effective Ignition System with Electrical System Setup in A Formula Student Racing Car. This project has been done step by step which is measuring, cutting, welding, grinding, assembling, and lastly is wiring process. In this setup, 2 batteries have been used for the electrical system setup. The first battery is used for the starter to start the engine. Meanwhile, the second battery is used to switch on the radiator fan which has been placed in the battery casing at the front of the chassis. This system needs 2 batteries because the engine needs more current to start the starter. This setup uses CDI racing, rectifier, fuse, ignition coil, meter, ignition switch, and lastly spark plug. This component is needed to make sure the electrical setup functioning well. The meter panel and ignition switch have been placed on the panel board to allow the driver to start and see the meter indicator. This ignition and electrical setup is fabricated only for formula student racing cars